La indexación de las revistas contables en Colombia (2016)
This article presents some important aspects on accounting journals that are indexed under the parameters of the permanent indexing service (Publindex) of Colciencias, the purpose of this work is to identify the main criteria followed by such journals to obtain it.The paper points out the most important parameters to be considered to index a journal. Its starts from identifying the characteristics of accounting journals that currently are not indexed and compare them with the criteria and trajectories of two accounting journals that to date are indexed (one in C category and the other in A2 category), finally is studied in depth the case of the journal Activos and its trajectory for indexing in Publindex.